IDENTIFIKASI KOMPETENSI GURU SEBAGAI CERMINAN PROFESIONALISME TENAGA PENDIDIK DI KABUPATEN SUMEDANG - Fahdini, Reni; Mulyadi, Ence; Suhandani, Deni; Julia, Julia (Mimbar Sekolah Dasar, 2014)
This study aims to explore the professional competence of elementary school teachers certified in Sumedang district. The study was conducted in the form of a survey in urban areas Sumedang district with a population of 592 elementary school teachers and 60 teachers certified as research samples. Total Respondents are 180 people consisting of 60 persons certified elementary school teachers, 60 peers who have not been certified, and 60 principals who captured data through questionnaires. Data were processed and analyzed with the rating scale measurement techniques and SPSS 16, and obtained the following results: 1) rating scale analysis results indicate that the professional competence of certified teachers in the Sumedang district, four aspects are in the 'ENOUGH' category and one aspect is in the 'LESS' category, and 2) the results of the attitude scale analysis using SPSS 16 shows that the professional competence of certified teachers in the Sumedang district are in 'GOOD' category, but this condition is far from the 'PROFESSIONAL' category.Keywords: competence, professional, teacher, certificated, sumedang.